Little Robot alone - MacLachlan, Patricia; Charest, Emily MacLachlan (Houghton Mifflin Harcourt, 2018)
When Little Robot finds a creative solution to his lonliness he gets straight to work on shaping the perfect companion out of metal, and affectionately names him Little Dog.